First-Principle Calculations of Structural, Elastic, and Electronic Properties of Intermetallic Rare Earth R2Ni2Pb (R = Ho, Lu, and Sm) Compounds - Benkaddour, Y.; Abdelaoui, A.; Yakoubi, Abdelkader; Khachai, Houari; Al-Douri, Yarub; Bin-Omran, Saad; Shankar, Amit; Khenata, Rabah; Voon, Chun Hong; Prakash, Deo; Verma, Keshav Deo (Springer Verlag, 2018)
The structural, elastic, and electronic properties of rare earth intermetallic R2Ni2Pb (where R = Ho, Lu, and Sm) compounds were investigated with the density functional theory (DFT) calculations. The calculations are performed using the full potential-linearized augmented plane wave (FP-LAPW) method within the framework of local density approximation (LDA). The calculated values of the equilibrium lattice constants were in agreement with the available experimental values. The elastic constants (Cij) were also calculated to understand the mechanical properties and structural stability of the compounds. Furthermore, the density of states and the charge density distributions of the compounds were calculated to understand the nature of the bonding in the material. The calculated results are in accordance with the available data in the literature.